Chemical and Organoleptic Study of Micro Green Based Functional Biscuits - , G K Rana, S P Mishra, Faruk Ansari, D K Pancheshwar, Yogendra Singh (Archives of Current Research International, 2025)
Aim: To study about functional foods and their importance to overcome malnutrition. Functional foods and their derivatives: they are not considered as medicines, so they do not have therapeutic effects on health. Bakery items, such as biscuits, are widely available and consumed by a large number of people in many countries, making them a viable supplementation vehicle for nutritional security. Methodology: The goal of the study was to designed and manufactured micro greeen-based biscuits by replacing refined wheat flour with micro green (Spinach) to combat malnutrition from a low-cost source as baked product for people at various levels (at 0, 05, 10, 15, 20 and 25 percent). Results: In terms of sensory qualities, the biscuits made with 90% refined wheat flour and 10% micro green (T3) were definitely the most palatable. Treatment T1 had the highest levels of CHOs, crude fat, fibre, protein, phosphorus, Iron and energy, while treatment T2 had the highest levels of ash, calcium, and moisture. Conclusion: Microgreens may prove to be a cost-effective and acceptable substitute for refined wheat flour in biscuit baking.